Domestic and school violence in short stature children with growth hormone deficiency - M.L. Aryayev; L.I. Senkivska (Medičnì Perspektivi, 2021)
The work is devoted to assessing the frequency of family (neglect, aggressive methods of punishment) and school (bullying) violence among short stature children with growth hormone deficiency (GHD) in comparison with children with normal growth.There were 94 children with GHD in the main group at the age of 7.2±0.4 years. The control group included 310 healthy children aged 7.1±0.3 years. Signs of domestic violence (neglect, aggressive methods of punishment) and violence at school (school bullying) were identified by questioning children and parents. School bullying was assessed using The Olweus Bully/Victim Questionnaire, adapted in Ukrainian and Russian. To check the statistical hypothesis on differences of relative frequencies, in two independent samples, the criteria of хі-square (χ2) was used. No differences were found in the frequency of neglect in the main group (8.5%) compared to the control group (9.5%), p>0.05.  An equally low frequency of the use of non-aggressive methods of upbringing without physical and psychological punishment was found both in the main and in the control groups: 31.9% compared to 39.6% (p=0.25).There was no increased physical aggressiveness towards children with GHD: the frequency of physical punishment was 29.8% and did not differ from the control group by 35.3% (p=0.4). Psychological methods of punishment were used more often (38.3%) in the main group in comparison with the control group (25.1%); p=0.04.There was an increased frequency of school bullying in relation to children with GHD (27.2%: 18.1-36.3) compared with the control group (17.7%: 13.4-22.0), p=0.04. The frequency of school bullying in boys of the main group was 2 times higher than in boys of the control group. School bullying victims in the main group, compared with the control group, were more likely to feel depressed (30.8% versus 12.7%; p=0.05), less often had good friends (42.3% versus to 78.2%; p=0.001) and felt loneliness more often (26.9% in relation to 9.1%; p=0.04).